Public opinion and capital punishment in the United States - Jonson, Cheryl Lero (The Elgar companion to capital punishment and society, 2024)
For the first time in modern American history, more than half of the 50 states have halted the use of capital punishment through abolishment or governor-imposed moratoriums. Not only have states moved away from the practice, but the US also has experienced steep declines in the number of people being executed and sentenced to death. Additionally, support for capital punishment has fallen to a five-decade low. However, the majority of Americans still support the death penalty. As states continue to debate capital punishment, it is imperative to understand the public’s view of this policy, particularly in a time of larger criminal justice reforms. This chapter highlights historical trends in support; how demographic, cultural, and methodological factors impact support; and the concerns Americans have about the fair application and effectiveness of the death penalty. Understanding the public’s view may shed light on future trends in use of capital punishment in America.